The Influence of the Problem Based Learning (PBL) Model Assisted by PhET Simulation on Students' Learning Outcomes in Parabolic Motion Material - Molamahu, Dian; Buhungo, Trisnawaty Junus; Payu , Citron S.; Arbie, Asri (Kasuari: Physics Education Journal (KPEJ), 2025)
This study is motivated by the low learning outcomes of students on the topic of parabolic motion, which requires conceptual understanding and problem-solving skills. Conventional teaching models are often ineffective in helping students understand complex physics concepts. Therefore, this study examines the effect of the Problem Based Learning (PBL) model assisted by PhET Simulation on students' learning outcomes in parabolic motion. This research uses a quasi-experimental method with a One Group Pretest-Posttest design. The sampling technique is total sampling, with a sample consisting of 93 students from class XI Physics Specialization at SMA Negeri 1 Suwawa, academic year 2024/2025, with class XI A as the experimental class, XI C as replication 1, and XI B as replication 2. Data were collected through pretests and posttests using 10 essay questions that have been validated by experts and tested for validity and reliability. The results show that the average posttest score of the experimental class is 84.3, while the posttest scores for replication 1 and 2 are 82.9 each. T-test analysis confirms that students’ learning outcomes in the experimental class using the PBL model assisted by PhET Simulation are significantly higher than KKM of 70. The effect of this model is also evident from the course average normalized gain, which falls into the high category, namely 0.78 for the experimental class, 0.73 for replication 1, and 0.75 for replication 2. Furthermore, analysis of single student normalized gain and n-gain per cognitive aspect shows improvement in learning outcomes in the moderate to high category across all classes.